Culturally relevant reading books for Papua New Guinean children: Their reading rights and preferences. Issue 4 (December 2020) - Simoncini, Kym; Smith, Hilary; Gray, Lara Cain
Children have a right both to read and to see their lives mirrored in books. In this study we explored young Papua New Guinean children's reading preferences of 500 digital books. The books were created as part of a large project aimed at improving elementary (Preparatory to Year 2) children's literacy skills in Papua New Guinea. Reading materials are scarce in Papua New Guinea and typically offer children windows into other contexts. This was addressed through a collaborative approach with Papua New Guinean and international writers to develop culturally relevant books. Dashboard data from the digital library showing the 25 Most Read Books were collected from 321 girls and 369 boys in 7 pilot schools. The findings indicated that the children preferred fiction books that were culturally specific. There were no statistically significant gender differences in book choice. The findings from this study can help education departments and non-government organisations in the further development of children's books that will motivate children to read.